Median Rhomboid Glossitis: A Clinical and Microbiological Study - Goregen, Mustafa; Miloglu, Ozkan; Buyukkurt, Mustafa Cemil; Caglayan, Fatma; Aktas, Ayse Esin (European Journal of Dentistry, 2011)
Objectives: The purpose of this study was to investigate the relationship between median rhomboid glossitis (MRG) and Candida and bacteria species, prevalence and possible association with age, gender, smoking, denture wearing, and diabetes mellitus. Methods: Tongue examinations were performed on 4244 consecutive patients. Of all the examined patients, 30 diagnosed with MRG were selected as the study group and another 30 patients were selected as the control group, and these 2 groups were compared in terms of age and gender. Tongue cultures from these 60 patients were subjected to bacterial and mycological examinations. Results: MRG frequency was detected to be 0.7%. In mycological examination, Candida species were determined in 90.0% of the MRG patients and in 46.6% of the control group. This difference was statistically significant. Multivariate logistic regression indicated that diabetes mellitus and 20–39 years of age were significantly related to MRG. However, the association between MRG, gender, smoking, and 40–69 years of age was not statistically significant. Conclusions: It was determined that although there was a significant association between MRG, Candida and diabetes mellitus, the possible risk factors such as gender, smoking, and denture wearing for oral candidiasis were invalid for MRG. (Eur J Dent 2011;5:367-372)
Keywords: Candida; Median rhomboid glossitis; Diabetus mellitus